2017
DOI: 10.4314/ejhs.v27i2.7
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of knowledge of acute kidney injury among non-nephrology doctors in two government hospitals in Ondo City, Southwest, Nigeria

Abstract: BACKGROUND: Adequate knowledge of acute kidney injury (AKI) among doctors is essential for its prevention, early diagnosis and management. Assessing knowledge of AKI among doctors is necessary to identify areas of deficiencies and key areas to be emphasized when organizing educational programs aimed at improving AKI care. This study determined the knowledge of AKI among non-nephrology doctors in Ondo City, Southwest Nigeria. MATERIALS AND METHODS: This was a cross-sectional descriptive study carried out in two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 26 publications
1
14
0
Order By: Relevance
“…This finding is not unique to Rwanda, as the lack of adequate knowledge regarding clinical presentation, diagnosis, and management of patients with AKI has been previously documented in African countries. Studies in Malawi 30 and Nigeria 31 have reported knowledge gaps in both practicing doctors and nurses. Therefore, this emphasizes the need for ongoing training of clinicians to update their knowledge about diagnosis and management of AKI in developing countries.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is not unique to Rwanda, as the lack of adequate knowledge regarding clinical presentation, diagnosis, and management of patients with AKI has been previously documented in African countries. Studies in Malawi 30 and Nigeria 31 have reported knowledge gaps in both practicing doctors and nurses. Therefore, this emphasizes the need for ongoing training of clinicians to update their knowledge about diagnosis and management of AKI in developing countries.…”
Section: Discussionmentioning
confidence: 99%
“…Only 5% out of 169 physicians from Omdurman Military Hospital had so-called good AKI-related practice. Finally, Adejumo et al [ 23 ] found only 1.2% out of 82 physicians have good knowledge of AKI. In order to improve CKD-related health care at the Brandenburg University Hospital, a standardized educational program for physicians from all departments is indispensable.…”
Section: Discussionmentioning
confidence: 99%
“…In low income/resource limited countries, the knowledge of non-nephrologist has mostly been found to be modest. [ 15 , 16 ] Surprisingly, a study from the United Kingdom revealed that 37% of junior doctors were not able to name a single indication of AKI for nephrology referral. [ 17 ] From Saudi Arabia, variations were reported in the knowledge of risk factors and assessments for AKI among healthcare professionals.…”
Section: Discussionmentioning
confidence: 99%